1996
DOI: 10.1016/s1074-7613(00)80298-8
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Hypermutation of Immunoglobulin Genes Is Linked to Transcription Initiation

Abstract: To identify DNA sequences that target the somatic hypermutation process, the immunoglobulin gene promoter located upstream of the variable (V) region was duplicated upstream of the constant (C) region of a kappa transgene. Normally, kappa genes are somatically mutated only in the VJ region, but not in the C region. In B cell hybridomas from mice with this kappa transgene (P5'C), both the VJ region and the C region, but not the region between them, were mutated at similar frequencies, suggesting that the mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
327
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(350 citation statements)
references
References 53 publications
22
327
0
1
Order By: Relevance
“…A connection between mutability and transcription has been noted in several studies (Betz et al, 1994;Peters and Storb, 1996;Goyenechea et al, 1997;Fukita et al, 1998) and Peters and Storb (1996) have proposed that transcriptional pausing may play a role in hypermutation. Transcriptional pause sites in c-MYC are amongst the best characterized of those in mammalian RNA polymerase II transcription units (Bentley and Groudine, 1986;Chung et al, 1987;Kerppola and Kane, 1988;Strobl and Eick, 1992;Keene et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A connection between mutability and transcription has been noted in several studies (Betz et al, 1994;Peters and Storb, 1996;Goyenechea et al, 1997;Fukita et al, 1998) and Peters and Storb (1996) have proposed that transcriptional pausing may play a role in hypermutation. Transcriptional pause sites in c-MYC are amongst the best characterized of those in mammalian RNA polymerase II transcription units (Bentley and Groudine, 1986;Chung et al, 1987;Kerppola and Kane, 1988;Strobl and Eick, 1992;Keene et al, 1999).…”
Section: Discussionmentioning
confidence: 91%
“…The V gene, whilst the physiological target of the mutation, is not needed for mutation recruitment: other sequences can be mutated in its place (Yelamos et al, 1995). Mutation recruitment depends upon the immunoglobulin transcription regulatory elements (Betz et al, 1994) with the location of the mutation domain being de®ned by the position of the transcription start site (Peters and Storb, 1996;Rada et al, 1997;Tumas-Brundage and Manser, 1997). Whilst the immunoglobulin loci are certainly the preferred targets of the hypermutation, the process is not wholly exclusive to them: BCL-6 (but not several other genes analysed) has been found to be a natural target for the hypermutation process ± albeit at a much reduced mutation rate (Migliazza et al, 1995;Pasqualucci et al, 1998;Shen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sequencing studies have revealed a sharp 5Ј mutation boundary delimited by the promoter, with mutation frequencies being highest in the coding exon and gradually diminishing to background levels over a 2-kb range (14 -17). Inserting an Ig promoter and leader immediately upstream of the constant region targeted mutations to a previously unsusceptible location (18). Similarly, increasing the distance between the Ig promoter and the V coding region did not change the overall frequency of mutations but did alter their distribution (19).…”
Section: Evolution Of Ig Dna Sequence To Target Specific Base Positiomentioning
confidence: 99%
“…The track of mutations coincides roughly with that of the transcribed 1-2 kb after the start site of transcription (2). The SHM process is initiated by the activationinduced cytidine deaminase (AID), which targets deoxycytidines (Cs) in cell-free assays in singlestranded DNA (3)(4)(5) and mainly in the nontranscribed strand during transcription of linear double-stranded DNA (6-10) but targets Cs on both DNA strands when they are flipped out in supercoiled DNA (11,12).…”
mentioning
confidence: 92%